Respostas
respondido por:
1
Vamos lá,
![f(x) = - 2x + 6 f(x) = - 2x + 6](https://tex.z-dn.net/?f=f%28x%29+%3D++-+2x+%2B+6)
na questão diz que quer encontrar f quando x=-4
![f( - 4) f( - 4)](https://tex.z-dn.net/?f=f%28+-+4%29)
É só substituir na equação, onde tem x coloca -4:
![f( - 4) = - 2( - 4) + 6 \\ > f( - 4) = 8 + 6 \\ > f( - 4) = 14 f( - 4) = - 2( - 4) + 6 \\ > f( - 4) = 8 + 6 \\ > f( - 4) = 14](https://tex.z-dn.net/?f=f%28+-+4%29+%3D++-+2%28+-+4%29+%2B+6+%5C%5C++%26gt%3B+f%28+-+4%29+%3D+8+%2B+6+%5C%5C++%26gt%3B+f%28+-+4%29+%3D+14)
na questão diz que quer encontrar f quando x=-4
É só substituir na equação, onde tem x coloca -4:
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás